Indonesia Language Speakers' Nonverbal Communication during Dental Treatment - Rianty Dwi Tantya, - (2011)
Nonverbal communication has a big role in the establishment of communication. It contributes almost 93% of idea in communication. This study entitled "Indonesia Language Speakers' Nonverbal Communication during Dental Treatment (a case study between Malaysian dentist and Indonesian patient during the dental treatment)" focuses on nonverbal languages used in particular condition, place and users. Communication between Indonesian patients and Malaysian dentists was observed in order to list, define and interpret what kinds of nonverbal languages used during medical treatment. On the other hand, this research also tries to figure out how the research participants' cultural background affects their establishment and the occurrence of misunderstanding in their nonverbal language. This study employs qualitative descriptive method. The data are gained from three Malaysian dentists and three Indonesian patients during the dental treatment. After observing and interpreting the data, the finding firstly reveals that some nonverbal languages occur during the dental treatment are eye contacts, facial expressions, and gestures. The distribution of each nonverbal language categories appeared to be as predicted by the literature. Secondly, misunderstanding rarely happens in the communication between Malaysian dentists and Indonesian patients. Finally, it is revealed that cultural background of the participants plays no significant role in affecting the communication between them.